2015
DOI: 10.1038/nm.3913
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils promote Alzheimer's disease–like pathology and cognitive decline via LFA-1 integrin

Abstract: Inflammation is a pathological hallmark of Alzheimer's disease, and innate immune cells have been shown to contribute to disease pathogenesis. In two transgenic models of Alzheimer's disease (5xFAD and 3xTg-AD mice), neutrophils extravasated and were present in areas with amyloid-β (Aβ) deposits, where they released neutrophil extracellular traps (NETs) and IL-17. Aβ42 peptide triggered the LFA-1 integrin high-affinity state and rapid neutrophil adhesion to integrin ligands. In vivo, LFA-1 integrin controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
707
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(793 citation statements)
references
References 61 publications
33
707
4
4
Order By: Relevance
“…Our data confirm that IgG alone is sufficient to increase phagocytosis in vitro and that delivery of IgG directly to the brains of Rag-5xfAD mice or into circulation via adoptive transfer can induce plaque clearance. Our study therefore adds to a growing area of research that highlights the importance of the peripheral immune system in CNS function and AD (17,18), and demonstrates the need to better understand how these peripheral cell populations act in concert with microglia to influence the CNS in both normal and diseased conditions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our data confirm that IgG alone is sufficient to increase phagocytosis in vitro and that delivery of IgG directly to the brains of Rag-5xfAD mice or into circulation via adoptive transfer can induce plaque clearance. Our study therefore adds to a growing area of research that highlights the importance of the peripheral immune system in CNS function and AD (17,18), and demonstrates the need to better understand how these peripheral cell populations act in concert with microglia to influence the CNS in both normal and diseased conditions.…”
Section: Discussionmentioning
confidence: 83%
“…However, the adaptive and innate immune systems rarely function independently of each other, and thus cross talk between peripheral and central immunity such as cytokine and chemokine signaling likely plays an important albeit understudied role in AD. In support of this notion, two recent studies demonstrated profound effects of peripherally derived neutrophils and T-regulatory cells (Tregs) on AD pathogenesis (17,18). Despite this exciting recent progress, many of the mechanisms and actions of other peripheral immune cell populations in AD remain unknown, and thus a great a deal of additional study is needed.…”
mentioning
confidence: 99%
“…Accumulations of Aβ in the periphery can similarly be phagocytosed by monocytes and neutrophils in the blood, and by macrophages in tissues 41 . Of note, in transgenic mice with AD, expression of Aβ scavenger receptors and Aβ-degrading enzymes in circulating mononuclear phagocytes decreases substantially as these mice age 42 , and the phagocytic functions of these cells are impaired in both mice and humans with AD [43][44][45] .…”
Section: Disorders Of Systemic Immunitymentioning
confidence: 99%
“…Using transgenic AD models, the extravasation of neutrophils into brain parenchyma to areas of amyloid plaques has been demonstrated [14,15]. At this time it is not known how IL-8 signaling contributes to the patterns of neutrophil infiltration in the AD animal models.…”
Section: Introductionmentioning
confidence: 99%